Unlocking Innovative Work Behavior: The Interplay of Engaging Leadership, Trust, Learning Climate, and Time Pressure - Tobias Kristianto; Yohana F. Cahya Palupi Meilani (Politeknik Siber Cerdika Internasional, 2026)
Background: In the era of Industry 4.0, companies must foster innovative work behavior (IWB) to sustain competitiveness. Yet even organizations with structured HRM systems report low work engagement among employees, particularly under high time pressure, creating a critical gap between innovation infrastructure and actual employee innovative behavior. Objective: This study examines the influence of engaging leadership, learning climate, trust, and time pressure on work engagement and, through it, on innovative work behavior, with work engagement as a mediating variable. Method: A quantitative cross-sectional design was employed. Using purposive sampling (criterion: minimum 2 years of service), data were collected via a five-point Likert scale questionnaire from 170 permanent employees at PT XYZ, a multinational manufacturing company in South Tangerang, and analyzed using PLS-SEM via SmartPLS 4.0. Result: The results of the study show that engaging leadership and learning climate have a positive and significant effect on work engagement, while trust and time pressure have no significant effect. In addition, work engagement has been proven to have a positive effect on innovative work behavior. The indirect relationship of engaging leadership and learning climate with innovative work behavior is established through work engagement mediation, while trust and time pressure are not mediated by work engagement. Conclusion: These findings affirm engaging leadership and a positive learning climate as the primary drivers of work engagement and innovation. Organizations should strengthen an engaging culture, broaden learning opportunities, and frame time pressure as a motivating challenge rather than a hindrance.